The sexual and reproductive healthcare challenges when dealing with female migrants and refugees in low and middle-income countries (a qualitative evidence synthesis) - Tadele Dana Darebo; Mark Spigt; Berhanetsehay Teklewold; Abebe Sorsa Badacho; Niklas Mayer; Meba Teklewold (BMC, 2024)
Abstract Background Migrants and refugees face unprecedented inequalities in accessing sexual and reproductive health (SRH) in developed and developing countries. Most attention has focused on the rich world perspective, while there are huge numbers of migrants and refugees moving towards less developed countries. This article synthesizes the barriers to proper SRH care from low and middle-income countries perspective. Methods We performed a systematic review of articles containing primary source qualitative and quantitative studies with thick qualitative descriptions. Articles from various databases, including PubMed, Science Direct, HINARI, and Google Scholar, published between 2012 and 2022 were included. Because the context differed, we excluded articles dealing with migrants and refugees from low- and middle-income countries living in high-income countries. To select articles, a preferred reporting item for systematic reviews and meta-analyses (PRISMA) was used. The articles' quality was assessed using the standard QASP checklist. We used a socio-ecological model to investigate barriers at various levels, and thematic analysis was used to identify the strongest themes at each level of the model. This synthesis is registered under PROSPERO number CRD42022341460. Results We selected fifteen articles from a total of 985 for the final analysis. The results show that despite the diversity of the participants' homes and countries of origin, their experiences using SRH services were quite similar. Most female migrants and refugees claimed to have encountered discrimination from service providers, and linguistic and cultural obstacles played a significant role in their experiences. In nations lacking universal healthcare coverage, the cost of care was a barrier to the use of SRH services. Other main obstacles to using SRH services were a lack of knowledge about these programs, worries about privacy, inadequate communication, stigma in the community, and gender-related power imbalances. Conclusion To enhance the use of SRH by female migrants and refugees, it is vital to provide person-centered care and involve husbands, parents, in-laws, and communities in SRH coproduction. Training on cultural competency, compassion, and respect must be provided to healthcare personnel. Increasing financial access for migrant and refugee healthcare is crucial, as is meeting their basic requirements.